Hospitalization for migraine and other headache syndromes at Walter Cantídio University Hospital between 2018 and 2022: an epidemiological analysis - Sousa, João Marcelo Albuquerque Beserra De; Junior, Francisco Duque de Paiva Giudice; Melo, Leonardo José Rodrigues de Araújo; Aureliano, Kauane Emily Ribeiro; Cavalcante, Francisco Luciano Honório; Davi, Emanuela Freire Caetano; Rodrigues, Pedro Vitor Ferreira; Santos, Leonardo Elias Araujo dos; Tavares, Mariana Alcântara; Rosa, Rodrigo Fagundes da; Sousa, Bruno Henrique Alcântara Lopes de (Headache Medicine, 2023)
Full abstract in PDF.